Firm Size, Board Size, And Ownership Structure And Risk Management Disclosure - Dwi Pangestuti; Erika Takidah; Ratna Anggraini ZR (Jurnal Akuntansi dan Keuangan Islam, 2017)
This research aims to examine the influence of firm size, board size, and ownership structure on risk management disclosure on syariah banking in Indonesia 2011-2014. This research uses secondary data which is the annual report of syariah banking. The sample was selected by purposive sampling which are 10 syariah banking qualified in this research. This research conducts multiple linear regression analysis method to examine the hypothesis in the level of significance 5%. The result of this research showed that firm size, board size and public ownership have influence on risk management disclosure. Meanwhile, the institutional ownership didn’t have a significant impact on risk management disclosure